2023
DOI: 10.1186/s13058-022-01601-4
|View full text |Cite
|
Sign up to set email alerts
|

On-treatment derived neutrophil-to-lymphocyte ratio and survival with palbociclib and endocrine treatment: analysis of a multicenter retrospective cohort and the PALOMA-2/3 study with immune correlates

Abstract: Background Cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors have been established as a standard treatment for hormone receptor (HR)-positive, human epidermal growth factor receptor 2 (HER2)-negative advanced breast cancer (ABC); however, predictive biomarkers with translational relevance have not yet been elucidated. Methods Data from postmenopausal women who received the CDK4/6 inhibitor palbociclib and letrozole for HR-positive, HER2-negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Interestingly, Kim et al determined NLR after one treatment cycle with high NLR to predict a reduced PFS 49 , 50 . However, this strategy is not usable for therapy decision making, because a predictive marker has to be evaluated before therapy start.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Kim et al determined NLR after one treatment cycle with high NLR to predict a reduced PFS 49 , 50 . However, this strategy is not usable for therapy decision making, because a predictive marker has to be evaluated before therapy start.…”
Section: Discussionmentioning
confidence: 99%
“…Standard treatment for osteosarcoma patients includes 2-3 cycles of neoadjuvant chemotherapy prior to surgery, which inevitably affects the patient's immune cell population (35). However, previous studies have shown that the degree of chemotherapy's impact on different immune cells is not consistent, with a greater reduction observed in neutrophils compared to lymphocytes (29). This leads to a decrease in delta NLR in most patients with high baseline NLR, and the poor prognosis of patients with high baseline NLR is already widely recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, NLR research is the most extensive and has been incorporated into the latest guidelines for the diagnosis and treatment of urological system tumors (15,(23)(24)(25)(26). Although most studies examining the role of NLR in cancer have focused on baseline values, recent evidence suggests that the dynamic changes in NLR during treatment may be more informative in predicting patient prognosis (27)(28)(29). Chronic inflammation and immune dysfunction are hallmarks of cancer, and NLR reflects the interaction between these two processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the emergence of immune therapies, such as immune checkpoint inhibitors (ICI), T cells have become a central focus in engaging the immune system in battle against cancer (1). Previous studies have revealed that lymphopenia (2), including anti-cancer treatment-induced lymphopenia, is associated with inferior survival outcomes (3)(4)(5). Furthermore, a low response to ICI therapy has been observed in patients with low lymphocyte count (6).…”
Section: Introductionmentioning
confidence: 99%